New insights on the utilization of ultrasonicated mustard seed cake: chemical composition and antagonistic potential for root-knot nematode, Meloidogyne javanica - NADEEM, Hera (Zhejiang University Press, 2021)

(untitled) (J Zhejiang Univ Sci B)
This study focused, for the first time, on the effect of ultrasonic features on the extraction efficiency of secondary metabolites in mustard seed cake (MSC). The nematostatic potential of sonicated seed cake was examined against the second-stage juveniles (J2s) of root-knot nematode, Meloidogyne javanica. The results show that a 35 ppm (parts per million) concentration of a sonicated extract (SE) sample of MSC caused 65% J2s mortality at 18 h exposure period in vitro. It also significantly suppressed the root-knot index (RKI=0.94) in tomato roots. The lethal concentration values for SE were 51.76, 29.79, and 13.34 ppm, respectively, at 6, 12, and 18 h of the exposure period, and the lethal concentration values for the non-sonicated extract (NSE) sample were 116.95, 76.38, and 55.59 ppm, respectively, at similar exposure time. Sinapine and gluconapin were identified as the major compounds in ultrasonic-assisted MSC. Because of the high extraction efficiency of metabolites in the SE, all treatments of SE were shown to be antagonistic to J2s. Thus, this study of ultrasonication activity-based profiling of MSC may help generate target-based compounds at a scale relevant to the control of disease caused by nematodes in economic crops.